Understanding the hidden burden: prevalence and factors linked to left ventricular hypertrophy in hypertensive patients receiving care in Harari region, Ethiopia - Tadesse, Ashenafi; Ayele, Zerihun Abera; Mekonnen, Megnot Hailu; Mesfin, Sinetibeb; Abebe, Dawit (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLeft ventricular hypertrophy (LVH) is often a complication of hypertension and an independent risk factor for cardiovascular events. In Ethiopia, there is a scarcity of data on the prevalence and associated factors of left ventricular hypertrophy among hypertensive adults. This study aimed to assess the prevalence and associated factors of left ventricular hypertrophy among adult patients with hypertension attending treatment at two public hospitals in Harar, Eastern Ethiopia from 20 December 2021 to 20 December 2023.MethodA hospital-based cross-sectional study was conducted on 264 hypertensive patients from 20 December 2021 to 20 December 2023. A pretested structured questionnaire and checklist were used to collect data from participants and their clinical records. The data were collected by trained residents and interns. Data were analyzed using SPSS version 29. Left ventricular mass was measured by transthoracic echocardiography. Associations between categorical variables were assessed using a chi-square test and odds ratio with 95% confidence interval. A logistic regression model was used to identify risk factors of LVH. p-values of <0.05 were considered as statistically significant.ResultsThe study included 264 adults with hypertension, with a mean age of 58.4 years, and the majority (54.5%) were male. The prevalence of echocardiographically confirmed left ventricular hypertrophy (LVH) was 30.7% (95% CI: 25.1%–36.3%), with mild LVH being the most common type (51%). Significant predictors of LVH included age over 60 years [adjusted odds ratio (AOR) = 5.981, CI = 1.832–19.522, p = 0.003], khat chewing (AOR = 2.676, CI = 1.786–9.109, p = 0.001), diabetes (AOR = 10.430, CI = 2.904–37.454, p < 0.001), poor medication adherence (AOR = 4.132, CI = 1.208–14.141, p = 0.024), uncontrolled systolic blood pressure (AOR = 8.340, CI = 2.280–30.512, p = 0.001), lack of home blood pressure monitoring (AOR = 5.591, CI = 1.041–30.012, p = 0.045), and longer hypertension duration (AOR = 8.766, CI = 2.101–36.584, p = 0.003). These findings emphasize the need to address modifiable risk factors in managing hypertension to reduce the burden of LVH.ConclusionsThe echocardiographic prevalence of LVH was 30.7% in the study population. These results highlight the importance of addressing modifiable risks to reduce LVH burden.